2002
DOI: 10.1038/sj.ijo.0801900
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical training on body composition and organ weights in ovariectomized and hyperestrogenic rats

Abstract: OBJECTIVE:To investigate whether regular endurance-type exercise can benefit rats submitted to a model of ovariectomy (OVX)-induced obesity with or without estrogen replacement. SUBJECTS: OVX Sprague-Dawley rats were compared to an ovariectomized-estradiol-treated group (OVXE2) and a Shamoperated (Sham) group. Each of these groups were subdivided into a sedentary and a treadmill-trained (8 wk) group. DESIGN AND MEASUREMENTS: An experimental study in which various parameters, including fat depots, blood lipids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
41
3
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 31 publications
14
41
3
6
Order By: Relevance
“…Progressive fat accumulation induces oxidative stress and was proven to cause obesity, hypertension and cardiovascular diseases (Park et al 2016). Previous study observed the weight gain in the ovariectomised rats are due to the oestrogen deficiency resulting an increase in the fat accumulation (Latour et al 2001, Shinoda et al 2002. However, the findings are not in line with the present results as Ovx+N group did not show any significance increase in the body weight compared to the sham group.…”
Section: Discussioncontrasting
confidence: 88%
“…Progressive fat accumulation induces oxidative stress and was proven to cause obesity, hypertension and cardiovascular diseases (Park et al 2016). Previous study observed the weight gain in the ovariectomised rats are due to the oestrogen deficiency resulting an increase in the fat accumulation (Latour et al 2001, Shinoda et al 2002. However, the findings are not in line with the present results as Ovx+N group did not show any significance increase in the body weight compared to the sham group.…”
Section: Discussioncontrasting
confidence: 88%
“…To estimate the bone mineral density of the proximal metaphysis of the tibia, computer-assisted tomography (CT) allowed determination of trabecular density of the metaphysis of the tibia. It is well documented that loss of estrogens results in increased fat accumulation in animals (23). In the same CT plane in which the tibial metaphysis was scanned a paratibial fat depot was visible, the surface of which could also be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 22 studied OVX and SHAM SpragueDawley rats and found that OVX reduced calcium absorption and balance, resulting in increased excretion of fecal calcium. They also found that OVX animals gained more weight, a fact reported in the literature for humans and animals 22,25 attributed to hormonal disorder and greater fat accumulation. Kobayashi et al 23 reported that Fisher rats had lower calcium balance than SHAM rats due to low intestinal absorption eight weeks after ovariectomy.…”
Section: Discussionmentioning
confidence: 65%